Role stress and psychological empowerment as antecedents of job satisfaction - Orgambídez-Ramos, Alejandro (2017)
The aim of this study was to examine the impact of role stress (ambiguity and conflict) on job satisfaction through psychological empowerment in the workplace. Data was collected from 314 workers from southern Portugal (M = 35.39, SD =10.66; 69.75% women) age age Results indicated that role conflict had a direct effect on job satisfaction, while the impact of role ambiguity on job satisfaction was totally mediated by meaning and self-determination. Psychosocial interventions in companies should focus on prevention of role stress and pro motion of psychological empowerment in the workplace.